Identification of MHC Class II Immunopeptidomes from Shigella flexneri 2a-infected Macrophages as Potential Vaccine Candidates - Nor Raihan Mohammad Shabani; Che Muhammad Khairul Hisyam Ismail; Chiuan Herng Leow; Munirah Mokhtar; Kirnpal Kaur Banga Singh; Chiuan Yee Leow (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Shigella is a Gram-negative rod-shaped intracellular bacterial pathogen that causes bacterial dysentery or shigellosis among children under five years old. Antibiotics have been less effective in treating shigellosis due to the multi-drug resistance of Shigella. Therefore, an effective vaccine is urgently needed to prevent this disease. The present study aims to determine the peptides presented by major histocompatibility complex (MHC) class II molecules of Shigella-infected macrophages using mass spectrometry-based immunopeptidomics approaches. The MHC class II-associated peptides derived from Shigella-infected macrophages are candidates for developing subunit-based Shigella vaccine.METHODS: THP-1-derived macrophages were infected with Shigella flexneri 2a at the multiplicity of infection equal to 10. The lysate was immunoprecipitated and analyzed by liquid chromatography–tandem mass spectrometry (LC-MS/MS). The sequences retrieved were analyzed using bioinformatics tools.RESULTS: The Shigella-infected THP-1-derived macrophages contained sample peptides from source proteins of almost all subcellular localizations. Eight peptides from S. flexneri 2a-infected macrophages were predicted to be localized at the outer membrane proteins (OMPs) of S. flexneri 2a by the PSORTb server. Two of the OMP-associated peptides were predicted as antigenic, non-allergenic, and non-toxic by respective bioinformatics tools.CONCLUSION: The findings in this study showed two selected OMPs have great potential for vaccine development against shigellosis.KEYWORDS: immunopeptidomics, mass spectrometry, vaccine development, Shigella, MHC peptides